Trends in activities of daily living disability in a large sample of community-dwelling Chinese older adults in Hong Kong: an age-period-cohort analysis. Issue 12 (15th December 2016) - Yu, Ruby; Wong, Moses; Chang, Billy; Lai, Xin; Lum, C M; Auyeung, T W; Lee, Jenny; Tsoi, Kelvin; Lee, Ruby; Woo, Jean
Abstract : Background: To examine the trends in activities of daily living (ADL) disability in older Chinese adults in Hong Kong between 2001 and 2012. Methods: Using data from the Elderly Health Centres (EHCs) of the Department of Health comprising a total of 54 808 community-dwelling Chinese adults aged ≥65 years in 1 early cohort (1904–1917) and 10 3-year birth cohorts (1918–1920, 1921–1923, 1924–1926, 1927–1929, 1930–1932, 1933–1935, 1936–1938, 1939–1941, 1942–1944, 1945–1947), we examined trends in ADL disability by using age-period-cohort (APC) models. ADL disability was defined as being unable to perform at least 1 of 7 ADL activities (bathing, dressing, toileting, transferring, feeding, grooming, walking) independently. Cross-classified random-effects logistic regressions were performed for each of the APC trends with adjustment for age, period, cohort, sociodemographic, lifestyle, comorbidity and self-rated health. Results: The mean age of the cohort was 70.9±4.7 (range 65–99) years. The prevalence rate of ADL disability was 1.6%. ADL disability increased with age (p<0.001) and the gradient of the increase was steeper in the older age groups. At the same age, women (1.7%) were more likely to report ADL disability than men (1.4%, p=0.001). For both genders, there was an increase in ADL disability between 2003 and 2012; adjustment for age, cohort and other covariates has diminished the trends observed among men. There was no cohort effect in ADL disability. Conclusions: ADL disability in older adults has increased over the last decade. Further study is required to identify possible causes behind the disability trends.